LIFELONG SEGREGATION BY PRISON SENTENCE – PROS AND CONS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Occasional occurrence of severe criminal offences of sexual abuse of children and the disabled where the victims suffered lethal consequences has spurred a campaign for Criminal law amendment which requires that the extreme forms of such crimes may demand life sentence without possibility of parole. National Assembly of the Republic of Serbia has approved the amendments and accepted persistence on retribution despite the efforts made by the expert community and practitioners to express their disapproval and emphasize arguments against such drastic legal regulation. The dispute also refers to such way of punishment being in contrast to our obligation to accept international conventions, such as The Convention for the Protection of Human Rights and Fundamental Freedoms, The Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment and other certified international agreements, due to the fact that torture, inhuman or degrading treatment or punishment are forbidden under all circumstances. Additional argumentation is provided by the practice of European Court of Human Rights regarding life imprisonment, according to which countries which have signed the Convections are obligated to  ensure a legal procedure in their national legislation which makes life sentences, after maximum twenty five years from its beginning, subject to revision and inspection on whether any significant changes in the convict’s life have occurred and whether any improvement towards rehabilitation has been achieved which would render the continuation of the imprisonment unjustifiable by any penal explanation.  The aim of the paper is to refer to arguments both for and against legal regulation which favor retribution and discard the convicts’ rehabilitation despite empirical discoveries which indicate the counter-productiveness of such efforts.